UNIMAS online vacancy system - Fuang, Siew Yii (University Malaysia Sarawak (UNIMAS), 2001)
Information technology had brought a lot of changes to human life style. The business world for instance, computers and web pages are used as a tool for creating the e-commerce. The new phenomenon allows the Internet users to do their shopping activities at any time they want as long as they are able to get the connection from the Internet.